MOF-Derived Ni1−xCox@Carbon with Tunable Nano–Microstructure as Lightweight and Highly Efficient Electromagnetic Wave Absorber - Wang, Lei; Huang, Mengqiu; Yu, Xuefeng; You, Wenbin; Zhang, Jie; Liu, Xianhu; Wang, Min; Che, Renchao (Nano-Micro Letters, 2020)
Intrinsic electric-magnetic property and special nano-micro architecture of functional materials have a significant effect on its electromagnetic wave energy conversion, especially in the microwave absorption (MA) field. Herein, porous Ni1−xCox@Carbon composites derived from metal-organic framework (MOF) were successfully synthesized via solvothermal reaction and subsequent annealing treatments. Benefiting from the coordination, carbonized bimetallic Ni-Co-MOF maintained its initial skeleton and transformed into magnetic-carbon composites with tunable nano-micro structure. During the thermal decomposition, generated magnetic particles/clusters acted as a catalyst to promote the carbon sp2 arrangement, forming special core-shell architecture. Therefore, pure Ni@C microspheres displayed strong MA behaviors than other Ni1−xCox@Carbon composites. Surprisingly, magnetic-dielectric Ni@C composites possessed the strongest reflection loss value − 59.5 dB and the effective absorption frequency covered as wide as 4.7 GHz. Meanwhile, the MA capacity also can be boosted by adjusting the absorber content from 25% to 40%. Magnetic–dielectric synergy effect of MOF-derived Ni1−xCox@Carbon microspheres was confirmed by the off-axis electron holography technology making a thorough inquiry in the MA mechanism. Highlights: 1 MOF-derived porous Ni1−xCox@Carbon composites with tuning nano-micro structure were successfully synthesized. 2 Magnetic-dielectric synergy effect among the Ni1−xCox@Carbon microspheres was confirmed by the off-axis electron holography technology. 3 MOF-derived Ni@C microspheres displayed strong microwave absorption value of − 59.5 dB.